Bioaccumulation of heavy metals (Cadmium and Lead) in liver, gills and muscle of seawater fish Mugil cephalus from Benghazi lake and Qaminus beach, Libya. - El-Orfey, Tahany, A.; Jenjan, Hussein, B.; Gheryani, Nabeia, A.; Zoubi, Salha A. (Libyan Journal of Science &Technology, 2025)
The concentrations of heavy metals (Pb and Cd) were measured in the liver, gills and muscles of one hundred and sixty seawater fish of Mugil cephalus collected from two different areas (80 fish from Benghazi Lake and 80 fish from Qaminus beach) in the east of Libya. The levels of heavy metals diverse significantly between fish groups and organs (liver, gills and muscle). Gills always possessed the highest concentrations of two metals followed by liver and muscle. In all studied fish, the gills and livers were the target organs for lead and cadmium accumulation and the high accumulation of lead and cadmium in the gills and liver is likely linked to the roles of organs. Different groups of Mugil cephalus showed variations in metal concentrations. These concentrations of lead and cadmium in tissues were higher in groups collected from Benghazi Lake than in groups from Qaminus Beach. These differences among the two groups could be recognized as untreated pollutants that drifted directly to Benghazi Lake.